ULAMA MUSLIM KLASIK DI BIDANG ILMU AGAMA ISLAM: TEOLOGI, FIQH, TAFSIR, HADIS DAN TASAWUF - Bahrudin, Andre; Ismail, Fajri; Zuhdiyah, Zuhdiyah; Sukardi, Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This paper discusses the contributions of classical scholars to the development of Islamic religious sciences, including theology, fiqh, tafsir, hadith, and tasawuf. The background of this research focuses on the importance of understanding the thoughts of classical Muslim intellectuals in the context of contemporary Islamic education. The method employed is a qualitative approach, collecting data through literature review and document analysis. The findings indicate that classical scholars, such as al-Ghazali and Ibn Khaldun, have created relevant and systematic methodologies in the study of religious sciences that can be applied in modern education. The discussion reveals that integrating Islamic values across various disciplines is crucial for shaping students' character and addressing contemporary challenges. The conclusion emphasizes the need to revitalize educational approaches that accommodate religious values and scientific knowledge, as well as the importance of continuing the intellectual legacy of classical scholars in facing today's complexities.